Thailand : The Politics of Despotic Paternalism - Thak Chaloemtiarana (Book collections on Project MUSE., 2007)
A narration of the volatile period following the second world war in which coups and counter coups become the common occurrence of political manoeuvring. Includes the Sarit regime, and explains the nature of Thai despotic paternalism and the concept of democracy seen within this context.